Determining the Technological and Pedagogical Content Knowledge Level of the 4th Grade Teachers on the Unit; Electric in our Life - Emre, İrfan; Çelik, Muhammed (Fırat University, 2021)
The aim of this stud is to determine the level of the technological and pedagogical context knowledge of the fourth grade teachers in a specific unit entitled “Electiricty in Our Life”. Total of 53 teachers from the three cities contributed to this study. In order to obtain more detailed information about teachers’ TPACK levels, a mixed research method with combination of both quantitative and qualitative data collection tools was employed. For data collection, four different data collection tools were used: Questionnaire of Nature of Science, Conceptual Test related to electricity, vignette and content representations. In addition, percentages, frequencies were calculated and Pearson’s correlation analysis technique was used. The results revealed that elementary teachers did not have sufficient knowledge about the content knowledge. Moreover, insufficient knowledge was also observed in teachers’ pedagogical knowledge, learning difficulties, assesments, and learning environment, which are the components of pedagogical content knowledge. Also, according to the results, teachers had limited knowledge in overall technology knowledge and subject-related technology knowledge.
Keywords: Other Fields of Education; Alan Eğitimleri